L'interaction de l'oral et de l'écrit: l'écriture automatique surréaliste - Füzesi, Piroska (Verbum – Analecta Neolatina, 2006)
In 1919, André Breton - a young psychiatrist, future leader of the surrealist movement - invents a new mode of expression to accurately convey the functioning of human thought: automatic writing. An automatic text is a monologue "on which the critical sense of the subject does not give any judgement" and which is "as exactly as possible the pronounced thought." He carries out his invention in writing in cooperation with Philippe Soupault. Their work entitled The Magnetic Fields is a book "without precedent," according to one of their friends, Louis Aragon. What is this work like, in which the 'told' and the 'written' are inseparably mixed? Is it rather an oral text or a written one? Does writing prove to be sufficient to convey the automatic act of oral nature? These are the questions which this paper attempts to answer.